SISTEM INFORMASI PENILAIAN GURU DAN PEMBINA PADA PONDOK PESANTREN AL-JAUHAR DURI - Candra Surya; Adi Asmandi (AMIK Mitra Gama, 2019)
The teacher and mentor assessment activities are a record of the assessment of the implementation of the teacher's and supervisor's duties in educating, teaching, training, directing, guiding and evaluating and evaluating students. With forms in the form of performance indicators related to the main tasks and functions of teachers and coaches. In the current assessment of teachers and supervisors at the Al-Jauhar Duri Islamic Boarding School, they have not yet used computers to process data. Although there are already computer equipment, but only limited to recording data only. where the assessment team still records manually using paper. so there are still shortcomings and errors, where the number of data values that must be processed, the complexity in processing a data, and the limited time spent in processing data. hence this will reduce the performance of the assessment team at Al-Jauhar Duri Islamic Boarding School. Based on this, the authors want to build an information system using the Visual Basic.Net programming language and MySQL database, which can simplify and accelerate the processing of teacher assessment and guidance data processing to make it faster and more accurate and use the Database. Keywords: assessment, teacher and coach, Visual Basic.Net and MySQL Database